2019
DOI: 10.1097/meg.0000000000001498
|View full text |Cite
|
Sign up to set email alerts
|

Trends in survival based on treatment modality for esophageal cancer: a population-based study

Abstract: Objectives The primary objective was to examine the trends in treatment modalities and the respective survival rates for esophageal cancer in the province of Ontario, Canada. Methods This is a population-based study of all esophageal cancer cases diagnosed in Ontario between 2007 and 2015, including squamous cell carcinoma and adenocarcinoma, with known disease stage. Other characteristics include sex, age, date of diagnosis, and treatment modalities. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
2
2
0
Order By: Relevance
“…The rate of OS shown in this study is comparable to previous studies, and this result suggests the reliability of using CGRD as the study material (Cheng et al, 2018;Akhtar-Danesh et al, 2019;He et al, 2020;Jung et al, 2020;Watanabe et al, 2021). Also, since guidelines recommend management based on multiple modalities for EC, the improvement in OS among CHM users provides the potential for using CHM as part of the management modalities for stage IV EC patients (Kitagawa et al, 2019;Muro et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The rate of OS shown in this study is comparable to previous studies, and this result suggests the reliability of using CGRD as the study material (Cheng et al, 2018;Akhtar-Danesh et al, 2019;He et al, 2020;Jung et al, 2020;Watanabe et al, 2021). Also, since guidelines recommend management based on multiple modalities for EC, the improvement in OS among CHM users provides the potential for using CHM as part of the management modalities for stage IV EC patients (Kitagawa et al, 2019;Muro et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…Also, since guidelines recommend management based on multiple modalities for EC, the improvement in OS among CHM users provides the potential for using CHM as part of the management modalities for stage IV EC patients ( Kitagawa et al, 2019 ; Muro et al, 2019 ). Akhtar-Danesh et al (2019) reported that the 5-year OS rate of stage IV EC patients was 0.8% with chemotherapy or radiotherapy alone, 5% with chemoradiotherapy, and 19.7% with surgical resection. A much better 5-year OS rate of stage IV EC was reported in Japan: 17.2% with definitive chemoradiotherapy and12.9% with radiotherapy alone ( Watanabe et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, for patients who underwent surgery, the 5-year overall survival rate significantly increased with an estimated cure rate ranging from 25% to 73%, depending on the tumor stage. Similar conclusions were also observed in the nationwide Swedish cohort study (36) and the populationbased study in Ontario, Canada (37). Ethnic disparities in EC-related survival were also reported, in which black patients with ESCC were found to have a poor prognosis in comparison with white and Asian/Pacific Islander race patients, even though these disparities decreased over time (38).…”
Section: Comparison With Other Studiessupporting
confidence: 77%
“…Almost half of all patients with esophageal cancer in North America present with a disease that is unresectable [ 1 , 2 ]. For the remaining 50%, the time to surgery (TTS) is of the utmost importance.…”
Section: Introductionmentioning
confidence: 99%